2016
DOI: 10.3390/app6090255
|View full text |Cite
|
Sign up to set email alerts
|

Flame Retardance and Smoke Suppression of CFA/APP/LDHs/EVA Composite

Abstract: Abstract:A new intumescent flame-retardants (IFR) system including the charing-foaming agent (CFA), ammonium polyphosphate (APP) and modified-layered double hydroxides (LDHs) with different transition metals (Ni, Co, Cu) were used in the ethylene vinyl acetate (EVA) matrix. Both the limiting oxygen index and the vertical burning tests indicate that the CFA/APP system and LDHs have significant synergistic flame retardant effects. The morphology of combustion residues indicates that the many pores of residues ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
7
1
Order By: Relevance
“…The average mass loss rate (AMLR) values of pure EVA and its composites are shown in Table NdMgAl/APP/CFA/EVA showed lower values of pk-HRR, THR, pk-SPR, and pk-COP. Furthermore, the pk-HRR, pk-SPR and pk-COP of S-LaMgAl/APP/CFA/EVA, S-CeMgAl/APP/CFA/EVA, and S-NdMgAl/APP/CFA/EVA were lower than those reported for APP/CFA/LDH/EVA without REEs [13].…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…The average mass loss rate (AMLR) values of pure EVA and its composites are shown in Table NdMgAl/APP/CFA/EVA showed lower values of pk-HRR, THR, pk-SPR, and pk-COP. Furthermore, the pk-HRR, pk-SPR and pk-COP of S-LaMgAl/APP/CFA/EVA, S-CeMgAl/APP/CFA/EVA, and S-NdMgAl/APP/CFA/EVA were lower than those reported for APP/CFA/LDH/EVA without REEs [13].…”
contrasting
confidence: 56%
“…The reported IFRs consisted of ammonium polyphosphate (APP) and CFA; when the mass ratio of APP and CFA was equal to 3:1, the EVA matrix had the best flame retardancy [12]. Moreover, composite flame retardants including APP, CFA, and LDH containing a transition element have been used to enhance the flame retardancy of EVA [13].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the most efficient flame‐retardant system for PLA is the combination of APP and the bio‐based charring agent such as lignin, starch, and β‐cyclodextrin (CD) . Moreover, numerous studies show that the addition of nanofillers to polymers could improve the flame‐retardant properties of the composites . Nanofillers such as montmorillonite, metal oxide, and graphene exert a flame‐retardant effect through forming the barrier layers, catalyzing the graphitization of polymers, and changing the decomposition pathway and decomposition behavior of the composites .…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22] Moreover, numerous studies show that the addition of nanofillers to polymers could improve the flame-retardant properties of the composites. 23,24 Nanofillers such as montmorillonite, metal oxide, and graphene exert a flame-retardant effect through forming the barrier layers, catalyzing the graphitization of polymers, and changing the decomposition pathway and decomposition behavior of the composites. [25][26][27][28] To reinforce the flame retardancy of PLA, In our previous work, three polyphosphazene/triazine bi-group molecules with different terminal groups were synthesized and used to prepare flame-retardant PLA composite combined with APP.…”
mentioning
confidence: 99%
“…Results showed that the obtained LDHs offered a significant improvement in the thermal stability, mechanical properties, and flame retardancy of polypropylene (PP) relatively to the unmodified LDHs. There were also researchers who not only use surfactant to modify LDHs, but also to replace the metal cations on LDH laminates for further increasing flame‐retardant performance . It was reported that when some of Mg elements in laminates were substituted by earth metal ions, the obtained LDHs exhibited higher flame‐retardant performance.…”
Section: Introductionmentioning
confidence: 99%